Hall-Petch relationship of interstitial-free steel with a wide grain size range processed by asymmetric rolling and subsequent annealing. (18th November 2020) - Fu, Bin; Pei, Chenghao; Pan, Hongbo; Guo, Yanhui; Fu, Liming; Shan, Aidang
Abstract: Asymmetric rolling (ASR) is an efficient processing for fabricating ultrafine-grained (UFG) materials. In the present investigation, interstitial-free (IF) steels with the grain size ranged from 500 nm to 500 μ m were obtained by asymmetric rolling and subsequent annealing. The evolution of microstructures and mechanical properties of IF steel were studied. Accordingly, the Hall-Petch relationship of IF steel with a wide grain size range was established. It was found that ultimate tensile strength (UTS) corresponds well to the Hall-Petch relationship over the whole grain size range. However, the yield strength (YS) and hardness deviated from the Hall-Petch relationship as the grain size is larger than 100 μ m, which is mainly attributed to the slight effect of grain boundary as obstacle on the dislocation movement and/or pile-up under small deformation in coarse grain (CG).